Perancangan Sistem Filling Rekam Medis di Rumah Sakit Umum Tabanan - Aditya, Made Wahyu Aditya; Ika Setya Purwanti (Jurnal IT UHB, 2025)
The efficiency of medical record management plays an essential role in improving the quality and accuracy of hospital services. At Tabanan General Hospital, several issues were identified in the manual medical record filling process, including incomplete borrowing data and document return delays exceeding 24 hours. These problems were mainly caused by the use of manual expedition books, which are less effective and efficient. This study aims to design an electronic medical record filling system to support accurate and timely document management. The research employed a descriptive qualitative method combined with a waterfall design approach. The system design included the development of Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and user interface prototypes. The resulting system design is considered acceptable based on expert validation and is recommended for implementation at Tabanan General Hospital to improve efficiency, data completeness, and tracking accuracy in the medical record management process.